Associations of exposure to green space with problem behaviours in preschool-aged children. (29th November 2019) - Liao, Jiaqiang; Yang, Shaoping; Xia, Wei; Peng, Anna; Zhao, Jinzhu; Li, Yuanyuan; Zhang, Yimin; Qian, Zhengmin; Vaughn, Michael G; Schootman, Mario; Zhang, Bin; Xu, Shunqing
Abstract: Background: Limited evidence is available regarding the association of green-space exposure with childhood behavioural development. This study aimed to investigate the associations of exposure to green space with multiple syndromes of behavioural development in preschool children. Methods: This cross-sectional study was conducted in Wuhan, China from April 2016 to June 2018. We recruited a sample of 6039 children aged 5–6 years from 17 kindergartens located in five urban districts of the city. We measured the greenness using average Normalized Difference Vegetation Index (NDVI) within a circular buffer area of 100 metres surrounding the central point of residences and kindergartens. We calculated the residence–kindergarten-weighted greenness by assuming that children spent 16 hours per day at home and 8 hours at kindergarten. The problem behaviours of children were evaluated at kindergarten using the Childhood Behavioral Checklist (CBCL) and standardized into problem behavioural T scores. Linear mixed-effect models and linear-regression models were used to estimate the associations. Results: We observed decreases in problem behaviours associated with kindergarten and residence–kindergarten-weighted surrounding greenness in preschool children. For example, a one-interquartile range increase in kindergarten and residence–kindergarten-weighted NDVI was associated with decreased T scores for total behaviour by −0.61 [95% confidence interval (CI): −1.09, −0.13) and −0.49 (95% CI −0.85, −0.12), anxiety and depression by −0.65 (95% CI: −1.13, −0.17) and −0.46 (95% CI: −0.82, −0.10), aggressive behaviour by −0.53 (95% CI: −1.01, −0.05) and −0.38 (95% CI: −0.75, −0.02) and hyperactivity and attention deficit by −0.54 (95% CI: −1.01, −0.07) and −0.48 (95% CI: −0.83, −0.12), respectively. Stratified analyses indicated that the associations of green-space exposure with problem behaviours were stronger in boys than in girls. Conclusions: Children attending kindergartens with higher levels of surrounding green space exhibited better behavioural development. The mechanisms underlying these associations should be explored further.